Processing and Utilization of Natural Phospholipids from Fish Belly Fat Waste of Jambal Siam Fish (Pangasius Hypophthalamus). Issue 1 (1st December 2022) - Ilza, M; Diharmi, A
Abstract: Phospholipids are used for food products, drug formulas, stabilizers, lubricants, cosmetics, pharmaceuticals, and emulsifiers. Synthetic phospholipids tend to be utilized for food and medicinal purposes, but nowadays consumer concern has shifted to phospholipids from natural ingredients. Phospholipids have functional properties towards health, consumer often requires phospholipids containing certain fatty acids such as omega 3. The purpose of this research is to process the belly fat waste of jambal siam fish into phospholipids and purify the phospholipids that are already obtained. The results showed that the highest saturated fatty acid content in jambal siam fish belly oil was palmitic acid which was expected to dominate the structure of phosphatidylglycerol, phosphatidic acid, and cardiolipin. The highest content of unsaturated fatty acids is oleic acid which was expected to dominate phosphatidylinositol, phosphatidyl ethanolamine, and phosphatidylcholine structure. The highest phospholipid content was phosphotidylcholine, followed by phosphatidylglycerol, diphosphatidylglycerol, phosphatidylethanolamine, and phosphatidylinositol. The hexane solvent produced a higher soluble hexane unsaturated fatty acid fraction than the insoluble hexane fraction, especially omega 6 and omega 9. While acetone produced higher levels of oleic acid and omega 3 soluble acetone, which was higher than the insoluble acetone. The higher the level of purity of phospholipids, the higher the content of oleic acid and omega 3.